Effect of Rate of Growth on Proportion of Tissues in Teak - Ramesh Rao, K.; Purkayastha, S. K.; Tandon, R. D. (Indian Forester, 1966)
Study of several consecutive growth rings in two samples of teak from Mysore and Kerala showed no definite relationship between ring width and proportion of tissues. The two samples also showed significant differences in proportion of tbaues though the average rate of growth is comparable.